Performance of Concrete Developed by Enhanced Gradation of Natural Fine River Sands by Partial Replacement of Waste Quarry Dust - Usman Akmal; Sana Fatima; Nauman Khurram; Qasim Shaukat Khan; Tauqir Ahmed; Hisham Alabduljabbar; Youssef Ahmed Awad (Advances in Civil Engineering)
As construction activity continues to increase on a daily basis, the demand for fine and coarse aggregates is also rising. However, relying on a few sources would quickly deplete the natural sources of aggregates. In Lahore, Punjab, Pakistan, costly coarse pit sand from northern areas is used for concrete, as the local river sands (Ravi and Chenab) are fine and do not meet ASTM specifications for fine aggregates. To alleviate the pressure on one source, it is necessary to improve the gradation of natural river sand by utilizing quarry dust obtained during the process of crushing rock into crushed stones. This study conducted detailed experimental work to enhance the gradation of natural river sand by adding normalized quarry dust. Concrete mixes with three strengths of 21 MPa, 28 MPa, and 35 MPa were prepared by partially replacing natural river sand with quarry sand. Workability and hardened concrete properties were evaluated for all mixes, and cost analysis was performed for 28 MPa concrete. The results were compared with control concrete made with coarse pit sand. When river sand was enhanced by combining 40% river sand and 60% normalized quarry dust, the resulting sand met ASTM requirements. Furthermore, when some fines were removed from river sand and replaced with 50% normalized quarry dust, the sand also met ASTM grading requirements. The compressive and flexural strengths of concrete made with enhanced sand gradation increased by 10–25% and 9–17%, respectively, for 28 MPa concrete compared to the control concrete. Cost analysis showed that 28 MPa concrete made with enhanced natural river sand gradation was 8.6% more economical than concrete made with coarse pit sand.